(untitled) (Journal of Nepal Geological Society, 2013)
Northeast Africa forms the northernmost extension of the East African Rift System and is considered one of the geodynamically active regions in the Earth. The Red Sea, Gulf of Suez, Gulf of Aqaba, and Dead Sea transform are the most prominent tectonic features in the region. Despite the motion of African and Arabian Plates being well-established, contribution of these plates to the origin of stress field in the Gulf of Suez has been under discussion. The main debate is on the controlling factors for the geodynamic origin of the Suez rift basin. The factors, either the present-day stress field is originated due to the Gulf of Suez rift itself or due to the influence of nearby tectonic boundaries, is under question. An attempt has been made to model the stress field of the area by 20 plane stress finite-element (FE) modeling incorporating realistic rock parameters and velocities for African and Arabian Plates. The modeled maximum horizontal stress (σHmax and minimum horizontal stress (σHmin) directions correlate well with observed stress indicators from the world stress map (WSM), focal mechanism solutions (FMS) of earthquakes, in-situ stress measurements, and geological stress information; and displacement field correlate well with GPS data of the region. Modeling result reveals that the present-day stress field in the Gulf of Suez is emerged from coeval influence of superimposed forces acting from rifting processes in the Red Sea, Gulf of Aqaba, and Dead Sea transform.